PUBLIC INVESTMENT CLOSES TRANSPORT INFRASTRUCTURE DEFICITS: EVIDENCE FROM PERU AND COLOMBIA, 2021-2023 - Naupari Machado, Fernando (2025)
Transport infrastructure deficits remain a structural constraint on economic and social development in Peru and Colombia. Although both countries expanded public investment to reduce these deficits, effectiveness is hindered by persistent obstacles: limited technical capacity, corruption, and planning that is rarely sustained in an integrated manner over time.  This article examines, for 2021–2023, how public investment (explanatory variable) relates to the closure of transport infrastructure deficits (outcome variable) and identifies the factors that condition its effectiveness. We adopt a quantitative, descriptive-comparative, non-experimental design. Evidence draws on surveys and interviews with sector experts in executing units, complemented by a documentary review of official and academic sources.  Findings show that budget execution alone does not ensure effective deficit reduction. In Peru, around 1,800 projects remain halted—about 30% of the transport portfolio— while in Colombia, weaknesses persist in the sustainability and maintenance of the road network and related infrastructure. Investment effectiveness is mediated by the quality of planning, the coupling between evaluation and execution, the technical competence of teams, and the robustness of control mechanisms. We argue that only an integrated and articulated approach can steer both countries toward a sustainable and equitable closure of transport infrastructure deficits.